Tectonostratigraphic analysis of the syn-rift infill in the Drava Basin, southwestern Pannonian Basin System. (June 2023) - Rukavina, David; Saftić, Bruno; Matoš, Bojan; Kolenković Močilac, Iva; Premec Fuček, Vlasta; Cvetković, Marko
Abstract: The Drava Basin in the SW Pannonian Basin System (PBS) was initially formed by passive rifting with accompanying sedimentary infill. Although this has been the subject of much previous work, an account of tectonic control has been lacking. Based on cores, wire logging, and seismic data, the tectonostratigraphic interpretation, depositional systems, and control on depositional systems of the syn-rift infill of the eastern part of the Drava Basin were studied. The rifting phase is characterised by the formation of half-grabens, grabens, a sag, and supradetachment basin structures with structural ramp and structural highs. The syn-rift infill can be divided into second-order tectonostratigraphic sequences corresponding to the early and late rift stages. The second-order sequences are further subdivided into third-order tectonostratigraphic sequences formed in response to higher-order tectonic events associated with local rift migration. In contrast to the early-stage structures, the late-stage rift structures are primarily controlled by extensional detachments that represent parts of the Drava Rift Fault System (DRFS). The early syn-rift is characterised by continental deposition through alluvial fans, fan deltas, and lacustrine environments. The late syn-rift stage is characterised by marine deposition in shallow water, fan deltas, and submarine slope-aprons, with deep marine sedimentation and intense volcanic activity. The ramp, basin slopes, and fault scarp slopes represent the major sediment transport pathways involved in the formation of alluvial fans, fan deltas, or submarine slope-aprons. Basinal sedimentation and major depocenters are located within synforms formed by structural lows in the geometry of extensional detachments. This study gives an example of syn-rift tectonic control for the SW part of the PBS and the influence of detachment geometry on basin fill. We have presented an approach based on 3D seismostratigraphic interpretation of tectonostratigraphic sequences, and the correlation of seismic facies with depositional environments developed in a back-arc setting. Highlights: The syn-rift infill of the Drava Basin is characterised by seismic facies and facies associations analysis. The early rift stage is characterised by continental deposition and the late rift stage is by marine deposition. Second-order and third-order sequences depict rift infill architecture. Tectonic forces were the main controlling factors during sedimentation.